Potential application of traditional Chinese medicine in age-related macular degeneration—focusing on mitophagy - Yu, Yujia; Wang, Gaofeng; Liu, Yong; Meng, Zhaoru (Frontiers in Pharmacology, 2024)
Retinal pigment epithelial cell and neuroretinal damage in age-related macular degeneration (AMD) can lead to serious visual impairments and blindness. Studies have shown that mitophagy, a highly specialized cellular degradation system, is implicated in the pathogenesis of AMD. Mitophagy selectively eliminates impaired or non-functioning mitochondria via several pathways, such as the phosphatase and tensin homolog-induced kinase 1/Parkin, BCL2-interacting protein 3 and NIP3-like protein X, FUN14 domain-containing 1, and AMP-activated protein kinase pathways. This has a major impact on the maintenance of mitochondrial homeostasis. Therefore, the regulation of mitophagy could be a promising therapeutic strategy for AMD. Traditional Chinese medicine (TCM) uses natural products that could potentially prevent and treat various diseases, such as AMD. This review aims to summarize recent findings on mitophagy regulation pathways and the latest progress in AMD treatment targeting mitophagy, emphasizing methods involving TCM.